2010
DOI: 10.1159/000289345
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Microembolic Signals and New Cerebral Infarcts on the Progression of Neurological Deficit in Acute Stroke Patients with Large Artery Stenosis

Abstract: Background: Early neurological deterioration is common in the acute phase after stroke. We sought to investigate the correlation between the progression of microembolic signal (MES), ischemic infarcts and the neurological deficits in the acute phase of stroke patients with large artery occlusive disease. Methods: Transient ischemic attack or stroke patients with relevant significant large artery stenosis (≧50% diameter reduction) and admitted within 7 days of the symptom onset were recruited in this study. MES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
(45 reference statements)
0
11
1
Order By: Relevance
“…The mRS score did not show statistical differences just before and 3 months after discharge (P = 0.319), suggesting that the presence of microemboli had no significant effect on the improvement of neurological function after 3 months. Hao et al (2010) found that the NIHSS score improved more significantly in patients with microemboli and turned negative in patients with continuously positive detection of microemboli. Iosif et al (2008) and Schlaug et al (1999) re-examined MRI DWI and perfusion-weighted imaging (PWI) on patients within 1 week after stroke onset and found that asymptomatic cerebral perfusion was more likely to decrease in microembolus-positive patients and that small infarct lesions that could not be detected with MRI DWI also emerged.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The mRS score did not show statistical differences just before and 3 months after discharge (P = 0.319), suggesting that the presence of microemboli had no significant effect on the improvement of neurological function after 3 months. Hao et al (2010) found that the NIHSS score improved more significantly in patients with microemboli and turned negative in patients with continuously positive detection of microemboli. Iosif et al (2008) and Schlaug et al (1999) re-examined MRI DWI and perfusion-weighted imaging (PWI) on patients within 1 week after stroke onset and found that asymptomatic cerebral perfusion was more likely to decrease in microembolus-positive patients and that small infarct lesions that could not be detected with MRI DWI also emerged.…”
Section: Discussionmentioning
confidence: 93%
“…These authors found that 43% of the patients were again detected as microemboluspositive one week later, and the total frequency of microembolus-positive patients in one week was 7%, which is close to our conclusion. Studies have shown that the ratio of microemboluspositivity peaks immediately after stroke, and the ratio decreases as time goes on (Sliwka et al, 1997;Iguchi et al, 2007;Hao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] MES have been used for risk stratification and assessment of therapeutic efficacy in these conditions. 4 Clopidogrel load (300 mg) combined with dual antiplatelet therapy reduces asymptomatic embolization in patients with symptomatic CARAS in 2 phase IIb randomized clinical trials.…”
Section: Icroembolic Signals (Mes) On Transcranial Dopplermentioning
confidence: 99%